Webtoon-Based Anticorruption Childrens Story Development - Saraswati, Gaharani; Soleh, Mirwan Aji; Dahlani, Awaliyah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2023)
The rise of corruption cases illustrates that Indonesia is experiencing a crisis of morals and trust. Seeing these conditions, efforts to eradicate anti-corruption are needed. One of them is through preventive efforts in the form of anti-corruption education from an early age. This research aims to 1) develop the webtoon CANTIK, 2) find out the feasibility of the webtoon CANTIK, and 3) find out the effectiveness of the webtoon CANTIK to introduce anti-corruption moral values to children. The research method used is research and development which consists of 4 stages: define, design, development, and dissemination. The content contained in CANTIK contains simple forms of corruption and anti-corruption values. The first series describes a form of bribery corruption with anti-corruption values: honesty, responsibility, independence, and courage. The second series describes the form of corruption of the time with anti-corruption values: discipline, care and justice. The third series describes the form of greed corruption with anti-corruption values: simplicity, hard work, and responsibility.